2018
DOI: 10.14201/eks20181936981
|View full text |Cite
|
Sign up to set email alerts
|

Estudio psicométrico de un cuestionario para medir la competencia digital de estudiantes universitarios (CODIEU)

Abstract: Para que la integración de las Tecnologías de la Información y la Comunicación (TIC) en las aulas universitarias contribuya al desarrollo de procesos pedagógicos de calidad, es necesario que los estudiantes posean un adecuado nivel de competencia digital. Para investigar esta competencia, necesitamos de instrumentos válidos y fiables que permitan recoger información sobre la misma. El principal objetivo que se pretende conseguir es el de identificar las propiedades psicométricas de un cuestionario para medir e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
(13 reference statements)
0
2
0
4
Order By: Relevance
“…Regarding the research on consensus mechanism of blockchain technology, Lázaro-Cantabrana et al [1] sorted out the academic research on consensus mechanism and compared the consensus mechanism of blockchain with the consensus mechanism of traditional technology. According to Casillas Martín et al [2], in the study of the combined application of blockchain and equity trading platform, the interests of investors can be more effectively maintained through smart contracts and consensus mechanisms.…”
Section: Research Statusmentioning
confidence: 99%
“…Regarding the research on consensus mechanism of blockchain technology, Lázaro-Cantabrana et al [1] sorted out the academic research on consensus mechanism and compared the consensus mechanism of blockchain with the consensus mechanism of traditional technology. According to Casillas Martín et al [2], in the study of the combined application of blockchain and equity trading platform, the interests of investors can be more effectively maintained through smart contracts and consensus mechanisms.…”
Section: Research Statusmentioning
confidence: 99%
“…Según Raygoza (2017) concluyo que las competencias digitales se limitan al dominio de herramientas como Word y Power Point, pero de los que están conscientes que es necesario adquirir un desarrollo de multialfabetización digital para que sean capaces de incluir contenidos que puedan ser sometidos a estudio para extraer de ellos información relevante que ayude a la adquisición de conocimientos. Para Casillas, et. al.…”
Section: Discussionunclassified
“…In this respect, in the review of the literature it was observed that there are few works in which valid and reliable instruments are shared that measure investigative competencies with respect to undergraduate training; even fewer are specific to the areas of health, and something that is missing as a fundamental dimension is the inclusion of technology as a basis for carrying out research nowadays [13,14]. Digital competencies have been measured and studied as a construct separate from the ability to carry out research or as an activity far removed from undergraduate students, with instruments with psychometric properties dedicated to assessing skills in postgraduate students [15][16][17][18][19].…”
Section: Measuring Competenciesmentioning
confidence: 99%